Kontribusi Aktivitas E-Commerce terhadap Timbulan Sampah: Studi Empiris di Kota Semarang - Wulandari, Royani; Maryono, Maryono; Umroh, Jamillatul (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2025)
This study analyzes the impact of e-commerce consumption on waste generation in Semarang City, specifically in Patemon Sub-district. The increasing dominance of e-commerce in the Industry 4.0 era has transformed consumer behavior and influenced household waste generation. This research used a quantitative approach through a survey of 100 e-commerce user respondents, and analyzes the relationship between variables using linear regression and the Sobel mediation test. This research evaluates waste generation as the dependent variable (Y), e-commerce consumption as the independent variable (X1), consumer behavior (I1) and environmental awareness (I2) as intervening variables.The analysis results indicate that e-commerce consumption has a positive effect on waste generation, with consumer behavior mediating this relationship. Conversely, environmental awareness does not exhibit a significant mediating effect. This study recommends promoting responsible consumption education, enhancing community-based waste management facilities, campaigning against waste burning, providing recycling incentives, and implementing regulations for eco-friendly packaging on e-commerce platforms to mitigate the negative environmental impacts of digital consumption